FINDING EQUIVALENCE LEVEL BETWEEN SOURCE LANGUAGE AND TARGET LANGUAGE - Akhmad Hairul Umam (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
Â This research study aims to investigate and identify the equivalence level of translation from textbooks using a qualitative approach with content analysis. As qualitative research, this study presented an analysis of the strategy made by the translator on how English text (Pretext for Mass Murder) was translated into Indonesian. The research study was started through observation of the source language that involved reading, identifying, classifying and evaluating the data. The collected data were analyzed descriptively under four main headings of equivalence level proposed by Mona Baker, namely in word level, above word level, grammatical level, and textual level equivalence. The sampling data of this research study is 150 sentences taken randomly, which are classified as word level (N=58, 39%), above word level (N=45, 30%), grammatical level (N=35, 30%), and textual level (N=12,8%). The findings demonstrated that the translator used different strategies creatively to find out the closest meaning of translation between the source language and the target language. In addition, word level equivalence was found to be the most dominant data compared to others.Â Keywords: translation, equivalence, the source language and target language.Â